Characterizing chlorotriazine effects in cancer-relevant high-throughput screening assays - Karmaus, Agnes L.; Charlton, Alex (Frontiers in Toxicology, 2025)
IntroductionHigh-throughput screening (HTS) in vitro testing can be a powerful tool for evaluating chemicals across an abundance of mechanistic, targeted assay systems. This study reviewed HTS in vitro data for the systematic evaluation of endpoints relevant to carcinogenesis. To these means, we focused on assay endpoints from the ToxCast/Tox21 HTS program that have been mapped to Key Characteristics of Carcinogens (KCCs) to help focus our review on the ∼750 assay endpoints that have been previously identified as potentially informative for evaluating modes of action relevant to carcinogenesis.MethodsData for ToxCast/Tox21 HTS assay endpoints were retrieved from the publicly accessible invitrodb v4.2 and reviewed for five chlorotriazine herbicides (atrazine, cyanazine, propazine, simazine, and terbuthylazine) to evaluate any indication of cancer-relevant bioactivity. More specifically, we present a workflow comprising the use of a focused assay endpoint inventory based on KCC attribution, integration of assay flags to identify robust bioactivity, and putting in vitro mechanistic insights into context with literature-based context for toxicokinetic considerations and in vivo evidence.Results and DiscussionThere were common targets consistently identified as bioactive across the chemical class including induction of estrone levels and potential CAR/PXR activation. These findings were put in context by utilizing in vivo data and knowledge about atrazine to weigh the evidence. Though the ToxCast/Tox21 HTS mechanistic assays did not yield novel insights into chlorotriazine carcinogenicity, our workflow exemplifies how starting from mechanistic screening data and integrating apical endpoints can be conducted. By providing context to in vitro ToxCast/Tox21 data with toxicokinetics information and available in vivo study outcomes demonstrates how the HTS data and KCC framework can be applied to review a chemical class for carcinogenicity potential.